The State of Social Safety Nets 2014 - World Bank (Washington, DC, 2014)
This publication begins a series that will monitor and report on social safety nets in developing countries. This first report in the series provides key social safety nets statistics and explains trends using information from 146 countries, including detailed household survey data from 69 countries in the World Bank's Atlas of Social Protection: Indicators of Resilience and Equity (ASPIRE) database. This report reviews important policy and practical developments in social safety net programs and highlights emerging innovations. While the primary focus is on developing and emerging countries, it also includes some references to high-income settings.